Źródła antyczne i nowożytne w diariuszu Mikołaja Krzysztofa Radziwiłła Sierotki (na przykładzie opisu kameleona) - Wiater, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2025)
The article examines how Mikołaj Krzysztof ‘the Orphan’ Radziwiłł incorporates works by both ancient and contemporary authors in his diary. A notable example is Radziwiłł’s description of a chameleon, which, while based on his personal observations, also reflects his reading of Pliny the Elder’s Natural History. It also includes early modern views on the chameleon, many of which were derived from ancient authors and repeatedly mediated through later sources.